Aqueous polyimide containing diaminomaleonitrile and dianhydride monomer copolymer, and preparation method and application thereof
By using aqueous polyimide containing diaminomalenitrile and dianhydride monomer copolymer as electrode binder in lithium-ion batteries, the problem of performance degradation caused by volume changes during lithiation of silicon-based electrodes is solved, and high mechanical strength, thermal stability and excellent cycling performance are achieved.
Patent Information
- Application Number
- CN202411705724.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-11
AI Technical Summary
The silicon-based electrodes used in existing lithium-ion batteries will undergo volume changes of up to 300% during the lithiation process, resulting in loss of electrical contact, increased internal resistance and loss of active substances, and seriously reducing cycling performance.
Aqueous polyimide containing diaminomalenitrile and dianhydride monomer copolymer is used as the electrode binder, and polar functional groups are introduced through copolyvinyl diamine to improve adhesion and ionic conductivity and enhance dynamic healability.
High mechanical strength and thermal stability are achieved, electrode expansion is effectively suppressed, and the circulation capacity and stability of lithium-ion batteries are improved.
Smart Images

Figure CN119591870A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a water-based polyimide containing a copolymer of diaminomaleonitrile and dianhydride monomers, a preparation method and application thereof. Background Art
[0002] The continuous depletion of fossil fuels and the growing demand for sustainable energy have prompted the development of affordable and high-performance energy storage systems. In this regard, rechargeable lithium-ion batteries (LIBs) have established a wide reputation in the transportation, aviation, and aerospace industries as a promising energy storage system due to their cycling stability, high power density, light weight, and low maintenance cost.
[0003] In recent years, the electric vehicle (EV) market has been driving demand for batteries with higher energy density and lower cost. At least greater than 350 Wh kg -1 and 750 Wh L -1 However, the theoretical specific capacity is 372 mAh g -1 Lithium-ion batteries consisting of a graphite anode and a lithium transition metal oxide (LTMO) cathode have almost reached their theoretical specific energy density of 350 Wh kg -1 Vertex [Adv. Funct. Mater. 2022, 32, 2110313].
[0004] Silicon has an extremely high theoretical energy density (4200 mAh g -1 ), the energy density of a single cell can reach 843Wh kg -1 , and at a low cost. Therefore, the use of silicon in lithium-ion batteries appears to be an attractive way to increase battery energy density and produce high-performance batteries. However, silicon-based electrodes undergo volume changes of up to 300% during lithiation (alloying), which can cause the silicon active material to break and fall off the copper current collector, resulting in loss of electrical contact, increased internal resistance and loss of active materials, which seriously degrades the cycling performance [Nano Lett. 2020, 20, 6922.].
[0005] From a practical point of view, the acceptable volume expansion rate of the electrode is about 10%, [6] which is comparable to the volume expansion rate of the carbonaceous anode used in current commercial lithium-ion batteries. To achieve the commercial viability of silicon-based anodes, researchers have adopted various approaches, including controlling the electrode porosity and the effective distribution of silicon, as well as the development of functional binders [Sci. Adv. 2020, 6, eaay5098.]. Considering efficient large-scale production and cost competitiveness, the use of highly functional polymer binder materials is considered to be the most effective way to mitigate the volume change of silicon anodes [Adv. Energy Mater. 2018, 8,1802107.]. Therefore, polymer binders with excellent mechanical strength have been developed, which can withstand large volume changes through van der Waals forces, supramolecular interactions (such as hydrogen bonds, ion-dipole interactions) or cross-linking bonds. However, most of the binders that have been developed are linear polymers, such as polyacrylic acid (PAA), sodium carboxymethyl cellulose (CMCNa), etc., which have the disadvantages of poor thermal stability and unstable chemical properties in extreme environments.
[0006] In order to overcome this shortcoming, the present invention introduces a water-soluble polyimide, which has excellent thermal stability and mechanical strength of polyimide and can effectively inhibit electrode expansion; and through copolymerization of polyethylene nitrile diamine, a large number of polar functional groups are introduced, which has excellent adhesion, ion conductivity and dynamic healing properties. Summary of the invention
[0007] The purpose of the present invention is to provide a water-based polyimide containing a copolymer of diaminomaleonitrile and dianhydride monomers, which has high thermal stability, excellent mechanical properties and excellent bonding properties, a preparation method and application thereof.
[0008] The present invention provides a water-based polyimide containing a copolymer of diaminomaleonitrile and dianhydride monomers, wherein the main chain is composed of a high molecular weight rigid aromatic skeleton and is combined with diaminomaleonitrile (DAMN) having a large number of nitrile polar groups and carbon-carbon double bonds, so as to obtain a high molecular weight polymer with excellent mechanical strength and the polarity of the nitrile group and lithium ion affinity. The obtained maleonitrile polyimide also demonstrates excellent chemical stability, film-forming properties and high adhesion strength.
[0009] To achieve the above object, the technical solution adopted by the present invention is:
[0010] A water-based polyimide (DAMN-PI) containing a copolymer of diaminomaleonitrile and dianhydride monomers, which is produced by reacting raw materials containing a dianhydride component and a diamine component, wherein the water-based polyimide comprises a copolymer of the following repeating structural units:
[0011]
[0012] Wherein, x+y=1, 0≤x≤1, 0≤y≤1; for example, x is 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1. For example, y is 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1.
[0013] A represents at least one of the following groups: a tetravalent organic group of an aromatic tetracarboxylic acid that does not contain fluorine, but does not contain a carboxyl group; a tetravalent organic group of an aliphatic tetracarboxylic acid that does not contain a carboxyl group; for example, A is at least one of the following groups:
[0014]
[0015] B represents at least one of the following groups: a divalent organic group of an aromatic diamine that does not contain fluorine, whose solubility in water is greater than 0.1 g / L (25°C) and does not contain an amino group; a divalent organic group of an aliphatic diamine, whose relative molecular mass does not exceed 500 and does not contain an amino group; for example, B is at least one of the following groups:
[0016]
[0017] M is an imidazole organic compound, which reacts with the carboxyl group of polyamic acid to form a water-soluble polyamic acid salt, and its structural formula is as follows:
[0018]
[0019] Wherein, X1 to X4 represent a hydrogen atom or an alkane group having less than 5 carbon atoms.
[0020] The preparation method of DAMN-PI of the present invention comprises the following steps:
[0021] (1) At room temperature, firstly dissolve diaminomaleonitrile (DAMN) and one or more diamine monomers of the diamine monomers containing a B group in deionized water, then add at least one of the imidazole organic compounds M to the solution, stir for at least 1 hour, and prepare a transparent solution, then add a dianhydride monomer containing an A group and dissolve it in the aforementioned solution, the molar ratio of the dianhydride to the diamine monomer is 0.9-1.3:1 (for example, the molar ratio of the dianhydride to the diamine monomer is 0.9:1, 0.92:1, 0.94:1, 0.96:1, 0.99:1, 1:1, 1.01:1, 1.02:1, 1.03:1, 1.05:1, 1.07:1, 1.09:1, 1:1, 1.1:1, 1.15:1, 1.2:1, 1.25:1 or 1.3:1), and the solution concentration is controlled at 10-30 wt%, the molar ratio of the imidazole organic compound M to the dianhydride monomer containing the A group is greater than 2 (for example, the molar ratio of the imidazole organic compound M to the dianhydride monomer containing the A group is 2, 2.5, 2.6, 2.8, 3, 3.2, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5 or 10);
[0022] (2) Under an inert gas environment, react the mixture in (1) for at least 6 hours to obtain an aqueous polyimide precursor solution.
[0023] The precursor solution of DAMN-PI obtained in the present invention can be used as an electrode binder in lithium-ion batteries, and comprises the following steps.
[0024] 1) Electrode manufacturing step: dissolve the negative electrode active material (including but not limited to silicon, graphite or silicon-carbon composite materials, etc.), conductive agent, and polyimide precursor solution in deionized water in a certain proportion, and mix them evenly using magnetic stirring and ultrasonic waves. Use a coating preparation device to evenly coat the slurry on one side of the current collector. The solid content of the polyimide precursor solution is not less than 1.5 wt %, and the loading amount of the negative electrode active material is higher than 0.5 mg cm -2 ;
[0025] 2) drying the coated electrode in a forced air oven at 60°C for 1-3 hours, and then transferring the electrode to a vacuum oven for treatment at a higher temperature (>120°C) for 2-12 hours to complete the imidization process of the polyimide precursor;
[0026] 3) The current collector after solvent drying is made into a circular electrode sheet with a diameter of 10-12 mm on a manual slicer. The mass of the electrode material on the electrode sheet can be calculated by weighing the mass before and after coating;
[0027] 4) Complete the installation of the lithium-ion battery buckle.
[0028] The aqueous polyimide precursor solution containing the copolymer of maleonitrile diamine and dianhydride monomers obtained in the present invention is used as a method for preparing a polyimide film, comprising the following steps:
[0029] 1) The obtained aqueous polyimide precursor solution containing maleonitrile diamine and dianhydride monomer copolymer is directly cast on a glass plate or a stainless steel plate, cast into a film at room temperature, dried at 60-100° C. for 5-24 hours to form a film, then vacuum dried at 80-120° C. for 5-24 hours, and vacuum treated at 150° C.-350° C. for 1-12 hours to complete the imidization process, thereby obtaining a polyimide film.
[0030] The beneficial results of the present invention are:
[0031] (1) The present invention discloses a water-soluble polyimide precursor solution with mild polymerization conditions and harmless solvents. It can be used to prepare polyimide containing maleonitrile components on the main chain;
[0032] (2) The precursor solution in (1) is used to prepare a polyimide having good mechanical strength and excellent battery performance;
[0033] (3) The polyimide prepared from the precursor solution in (1) above has excellent thermal stability, and the polymer decomposition temperature can reach 300-500°C;
[0034] (4) The polyimide precursor solution in (1) is used to prepare a negative electrode binder for lithium-ion batteries, and the resulting battery has excellent cycle capacity and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is the TGA curve of the polymer film prepared in Example 1.
[0036] Figure 2 This is the cycle performance curve of the silicon negative electrode prepared in Example 1 in a lithium-ion battery testing device. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is described in detail below through specific embodiments, but it should be clearly stated that these embodiments are for illustration and are not to be construed as limiting the scope of the present invention.
[0038] Example 1:
[0039] (1) In a 500 mL three-necked flask equipped with a nitrogen inlet and outlet, first dissolve p-phenylenediamine (PPD) (9.73 g, 0.09 mol) and diaminomaleonitrile (DAMN) (1.08 g, 0.01 mol) in deionized water, then add 1,2-dimethylimidazole (DMIZ) (24.03 g, 0.25 mol), and mechanically stir at 25 ° C for 1 h to prepare a transparent solution. Then add 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) (29.42 g, 0.1 mol) and dissolve it in the above solution. Mechanically stir at 70 ° C for 12 h, and the solution concentration is controlled at 15 wt%;
[0040] (2) The obtained aqueous polyimide precursor solution is directly cast on a glass plate or a stainless steel plate, cast into a film at room temperature, treated at 60°C for 1 hour, then vacuum treated at 120°C for 1 hour, and vacuum treated at 250°C for 30 minutes to complete the imidization process and obtain a polyimide film (60±5μm).
[0041] (3) Table 1 summarizes the properties of aqueous polyimide precursor solutions and polyimides.
[0042] The aqueous polyimide precursor solution of the present invention is applied to a lithium ion battery device, comprising the following steps:
[0043] 1) Prepare the negative electrode sheet of the lithium-ion battery. The anode is prepared as follows: Mix the aqueous polyimide precursor solution with deionized water, conductive carbon black (TIMCAL, Super C45), and nano-silicon (Canrd, 80-100nm) in a mass ratio of 10:10:80, and stir magnetically for 12-24 hours. After ultrasonic treatment for 30 minutes, apply the obtained slurry on the copper foil with a scraper (the coating thickness is 100um). Dry the prepared electrode at 60°C for 1 hour, and then vacuum treat it at 150°C for 6 hours to obtain a silicon negative electrode sheet;
[0044] 2) The current collector after solvent drying was made into a circular electrode sheet with a diameter of 12 mm on a manual slicer. The mass of the electrode material on the electrode sheet can be calculated by weighing the mass before and after coating; the loading amount of active material was controlled at 1.2 mg / cm 2 ;
[0045] 3) All battery assemblies were carried out in an argon atmosphere glove box, and the water and oxygen content in the glove box was less than 0.1ppm. The prepared electrode sheet was used as the working electrode, the metal lithium sheet was used as the negative electrode, and a mixture containing 1.0 M / L lithium hexafluorophosphate (LiPF6), 1:1 volume ratio of ethylene carbonate (EC) and diethyl carbonate (DEC) and 10% volume ratio of fluoroethylene carbonate (FEC) additive was used as the electrolyte. Figure 1 After the packaged button cell is left to stand for 12 hours, the cycle performance test can be carried out: after 2 cycles of activation at 1.0A / g, the test starts at 4.2A / g and the temperature is 25°C.
[0046] Figure 1 Thermogravimetric analysis curve of polyimide film prepared for Example 1: The polymer film (5 mg ± 0.5 mg) was loaded into a Discovery TGA thermogravimetric analyzer (Discovery TGA 55, TA Instruments Waters, USA), purged with N2, and the heating rate was 5°C / min, with a temperature range of 50°C-800°C. Figure 1 Analysis shows that the polyimide film obtained in Example 1 has excellent thermal stability, and the temperature of thermal weight loss of 5%wt is 526°C.
[0047] Figure 2 The cycling performance curve of the binder prepared for Example 1 and applied to the silicon-based half-cell was tested at 25°C. After 2 cycles of charge and discharge at 1.0 A / g, the battery was charged and discharged for 100 cycles at a high current density of 4.2 A / g. Even at a high current density of 4.2 A / g, the battery still had excellent cycle capacity and stability: after 100 cycles of charge and discharge, the battery still had a high capacity of 2084 mAh / g and a capacity retention rate of 60.0%.
[0048] Example 2:
[0049] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly dissolve p-PPD (8.65g, 0.08mol) and DAMN (2.16g, 0.02mol) in deionized water, then add DMIZ (24.03g, 0.25mol), and mechanically stir for 1h at 25℃ to prepare a transparent solution. Then add BPDA (monomer (29.42g, 0.1mol), and also dissolve it in the above solution, and mechanically stir for 12h at 70℃, and the solution concentration is controlled at 15 wt%; the rest of the experimental steps and application steps are the same as Example 1.
[0050] Example 3:
[0051] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, first dissolve p-PPD (6.49g, 0.06mol) and DAMN (4.32g, 0.04mol) in deionized water, then add DMIZ (24.03g, 0.25mol) and stir mechanically at 25℃ for 1h to prepare a transparent solution. Then add BPDA monomer (29.42g, 0.1mol), also dissolved in the above solution, stir mechanically at 70℃ for 12h, and control the solution concentration at 15 wt%; the rest of the experimental steps and application steps are the same as Example 1.
[0052] Example 4:
[0053] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, p-PPD (8.65g, 0.08mol) and DAMN (2.16g, 0.02mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25mol) was added and mechanically stirred at 25℃ for 1h to prepare a transparent solution. Then, 4,4'-oxydiphthalic anhydride (ODPA) monomer (31.02g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 70℃ for 12h, and the solution concentration was controlled at 15wt%; the rest of the experimental steps and application steps were the same as those in Example 1.
[0054] Example 5:
[0055] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, p-PPD (8.65g, 0.08mol) and DAMN (2.16g, 0.02mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25mol) was added and mechanically stirred at 25℃ for 1h to prepare a transparent solution. Then, 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) monomer (32.22g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 70℃ for 12h, and the solution concentration was controlled at 15wt%; the rest of the experimental steps and application steps were the same as those in Example 1.
[0056] Example 6:
[0057] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, p-PPD (8.65g, 0.08mol) and DAMN (2.16g, 0.02mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25mol) was added and mechanically stirred at 25℃ for 1h to prepare a transparent solution. Then, 3,3,4,4-diphenylsulfone tetracarboxylic dianhydride (DSDA) monomer (35.82g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 70℃ for 12h, and the solution concentration was controlled at 15wt%; the rest of the experimental steps and application steps were the same as those in Example 1.
[0058] Example 7:
[0059] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, p-PPD (8.65g, 0.08mol) and DAMN (2.16g, 0.02mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25mol) was mechanically stirred at 25℃ for 1h to prepare a transparent solution. Then, 2,3,3',4'-biphenyltetracarboxylic acid dianhydride (α-BPDA) monomer (29.42g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 70℃ for 12h, and the solution concentration was controlled at 15wt%; the rest of the experimental steps and application steps were the same as those in Example 1.
[0060] Example 8:
[0061] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, first dissolve p-PPD (8.65g, 0.08mol) and DAMN (2.16g, 0.02mol) in deionized water, then add DMIZ (24.03g, 0.25mol) and stir mechanically at 25℃ for at least 1h to prepare a transparent solution. Then add cyclobutanetetracarboxylic dianhydride (CBDA) monomer (19.61g, 0.1mol), which is also dissolved in the above solution, and stir mechanically at 60-80℃ for 6-18h, and the solution concentration is controlled at 10-30wt%; the rest of the experimental steps and application steps are the same as Example 1.
[0062] Example 9:
[0063] In a 500mL three-necked flask equipped with nitrogen inlet and outlet, firstly, 4,4'-diaminodiphenyl ether (ODA) monomer (16.02g, 0.08mol) and DAMN (2.16g, 0.02mol) were dissolved in deionized water, and then DMIZ (24.03g, 0.25mol) was added and mechanically stirred at 25℃ for 1h to prepare a transparent solution. Then, BPDA monomer (29.42g, 0.1mol) was added and dissolved in the aforementioned solution, and mechanically stirred at 70℃ for 12h, and the solution concentration was controlled at 15wt%; the rest of the experimental steps and application steps were the same as those in Example 1.
[0064] Comparative Example 1:
[0065] In this example, a polyimide precursor solution without DAMN during copolymerization was used as a comparative example: in an inert gas environment, firstly, PDA (10.81 g, 0.1 mol) was dissolved in deionized water, and then DMIZ (24.03 g, 0.25 mol) was added, and mechanically stirred for 1 h at 25°C to prepare a transparent solution. Then, BPDA (29.42 g) monomer was added and dissolved in the aforementioned solution, and mechanically stirred for 12 h at 70°C; the solution concentration was controlled at 15 wt%; the remaining experimental steps and application steps were the same as those in Example 1.
[0066] Comparative Example 2:
[0067] This example uses commercial polyacrylic acid (Aladdin, weight average molecular weight of 450,000) as a comparative example, and its application steps are the same as those of Example 1.
[0068] Comparative Example 3:
[0069] This example uses commercially available sodium carboxymethyl cellulose (DAICEL, CMC-2200) as a comparative example, and its application steps are the same as those of Example 1.
[0070] The following table lists the basic physical properties of the aqueous polyimide precursor solutions and polyimides prepared in all examples and comparative examples.
[0071] Table 1
[0072]
[0073] Table 1 Test method for data
[0074] Intrinsic viscosity dL g-1 test method: prepare the test sample into a 5 mg / L solution, use an Ubbelohde viscometer to measure the solvent retention time t0 / s and the test sample retention time t / s, and calculate the intrinsic viscosity according to the following formula:
[0075] ,
[0076] Rotational viscosity Pa s test method: Tested using a rheometer at 50°C;
[0077] Test method for glass transition temperature ℃: Prepare polyacrylic acid / polyimide composite film into 40mm The 8mm sample was loaded on a dynamic thermomechanical analyzer, and the measurement temperature range was 50-350°C, with a heating rate of 5°C / min. The glass transition temperature was obtained based on the changes in the storage modulus and loss modulus.
[0078] Elastic modulus Gpa Elastic strength Mpa Elongation at break % Test method: Prepare polyacrylic acid / polyimide composite film into 60mm The sample was 10 mm thick and loaded on a universal tensile testing machine with a tensile rate of 50 mm / min.
[0079] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A water-based polyimide (DAMN-PI) containing a copolymer of diaminomaleonitrile and dianhydride monomers, which is produced by reacting raw materials containing a dianhydride component and a diamine component, characterized in that: The water-based polyimide comprises a copolymer of the following repeating structural units: ; Among them, x+y=1, 0≤x≤1, 0≤y≤1; A represents at least one of the following groups: a tetravalent organic group of an aromatic tetracarboxylic acid that does not contain fluorine, but does not contain a carboxyl group; a tetravalent organic group of an aliphatic tetracarboxylic acid that does not contain a carboxyl group, for example, A is at least one of the following groups: ; B represents at least one of the following groups: a divalent organic group of an aromatic diamine that does not contain fluorine and does not contain an amino group; a divalent organic group of an aliphatic diamine whose relative molecular mass does not exceed 500 and does not contain an amino group; for example, B is at least one of the following groups: ; M is an imidazole organic compound with the following characteristics: ; Wherein, X1 to X4 represent a hydrogen atom or an alkane group having less than 5 carbon atoms.
2. The method for preparing the aqueous polyimide (DAMN-PI) according to claim 1, characterized in that: The steps include: (1) First, at room temperature, dissolving one or more of diaminomaleonitrile (DAMN) and diamine monomers containing a B group in deionized water, then adding at least one of imidazole organic compounds M to the solution, stirring for at least 1 hour to prepare a transparent solution, and then adding dianhydride monomers containing an A group and dissolving them in the aforementioned solution, wherein the molar ratio of the dianhydride monomers containing an A group to the diamine monomers containing a B group is 0.9-1.3:1, the solution concentration is controlled at 10-30 wt%, and the molar ratio of the imidazole organic compound M to the dianhydride monomers containing an A group is greater than 2; (2) Under an inert gas environment, react the mixture in (1) for at least 0.5 h to obtain an aqueous polyimide precursor solution.
3. Application of the aqueous polyimide (DAMN-PI) prepared by the method according to claim 2, characterized in that: The method is applied as an electrode binder in a lithium-ion battery, comprising the following steps: 1) Electrode manufacturing step: dissolving the negative electrode active material (including but not limited to silicon, graphite or silicon-carbon composite material, etc.), conductive agent, and polyimide precursor solution in deionized water and mixing them evenly; using a coating preparation device to evenly coat the slurry on one side of the current collector; the solid content of the polyimide precursor solution is not less than 1.5 wt %, and the loading amount of the negative electrode active material is higher than 0.2 mg cm -2 ; 2) The coated electrode is placed in a forced air oven at 60-110°C for drying for 0.1-3 hours, and then transferred to a vacuum oven or a tube furnace protected by an inert gas and treated at a higher temperature (120-350°C) for 0.1-12 hours to complete the imidization process of the polyimide precursor; 3) The current collector after solvent drying is made into a circular electrode sheet with a diameter of 10-14 mm on a manual slicer. The mass of the electrode material on the electrode sheet can be calculated by weighing the mass before and after coating; 4) Complete the installation of the lithium-ion battery buckle.
4. Application of the aqueous polyimide (DAMN-PI) prepared by the method according to claim 2, characterized in that: The steps include: The aqueous polyimide precursor solution is directly cast on a glass plate or a stainless steel plate, cast into a film at room temperature, dried at 60-100°C for 5-24h to form a film, then vacuum dried at 80-120°C for 5-24h, and vacuum treated at 150°C-350°C for 1-12h to complete the imidization process and obtain a polyimide film.